2021
DOI: 10.3177/jnsv.67.225
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Exercise and Intake of Amino Acid Mixture Synergistically Induces Beige Adipocyte Formation in Mice

Abstract: Exercise combined with dietary factors may have significant effects on the suppression of body fat accumulation. Several trials suggest that amino acid mixtures containing alanine, arginine, and phenylalanine (ARF) combined with exercise can significantly reduce body fat accumulation in overweight adults and high-fat diet-induced obesity in mice. We therefore hypothesized that combining ARF and exercise would significantly induce beige adipocyte formation and that this would contribute to reducing body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 55 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…As in our previous work, the exercise intensity was increased from 15 m/min in the first week, to 17.5 m/min in the second week, and to 20 m/min in the last 2 weeks. We previously confirmed that the exercise intensity and duration were unable to promote UCP1 expression in BAT and beige adipocyte formation in iWAT . In addition, preliminary experiments indicated that mice fed the 50β-Con diet alone for 4 weeks did not significantly induce beige adipocyte formation.…”
Section: Methodsmentioning
confidence: 69%
See 4 more Smart Citations
“…As in our previous work, the exercise intensity was increased from 15 m/min in the first week, to 17.5 m/min in the second week, and to 20 m/min in the last 2 weeks. We previously confirmed that the exercise intensity and duration were unable to promote UCP1 expression in BAT and beige adipocyte formation in iWAT . In addition, preliminary experiments indicated that mice fed the 50β-Con diet alone for 4 weeks did not significantly induce beige adipocyte formation.…”
Section: Methodsmentioning
confidence: 69%
“…Our mice were not fed a high-fat diet and are not a genetic model of obesity. It would be difficult to achieve significantly different results in body weight gain and adipose tissue deposits in C57BL/6 mice fed a normal diet, even if beige adipocyte formation was indeed induced in iWAT. ,, To specifically confirm the effect of exercise + 50β-Con-mediated beige adipocyte formation on fat deposits, the use is required of an animal model of obesity, such as mice fed a high-fat diet. Second, the exact molecular mechanism of the induction of synergistic beige adipocyte formation related to the combination of exercise and a 50β-Con diet needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations